Updated protocol: Effects of second responder programs on repeat incidents of family abuse: An updated systematic review and meta‐analysis. Issue 4 (10th November 2021) - Davis, Robert C.; Petersen, Kevin; Weisburd, David; Taylor, Bruce
Abstract: The US Department of Justice has extensively funded second responder programs. In England and Wales, funding of follow‐up with victims is largely funded by local Police and Crime Commissioners. While these programs rapidly gained popularity in the United States and are gaining popularity in other countries as well, the evidence regarding their effectiveness is mixed. Although some research has indicated that second responder programs can prevent repeat victimization, several experimental studies have suggested that these programs may actually increase the odds of abuse recurring. The purpose of the review is to compile and synthesize published and unpublished empirical studies of the effects of second responder programs on repeat incidents of family violence, including those studies completed after the original review. The Global Police Database (http://www.gpd.uq.edu.au/ ) provides a resource unavailable at the time of the initial review that will ensure that a comprehensive set of qualifying studies is identified. In the updated review, we will address the following questions: 1. What impact do second responder programs have on the number of subsequent calls to the police? 2. What impact do second responder programs have on abuse as measured on victim surveys? 3. Does the impact of second responder programs differ between experimental and quasi‐experimental studies or studies that employ different methods of drawing samples? Building on the original review, we also aim to expand our examination of effect size heterogeneity given sufficient data to do so. For instance, given the proposition that there may be only a small window of opportunity to intervene into the lives of family violence victims after an incident, the amount of time that elapses between a family violence call and the second response may be an important moderator of programmatic effects. Additional factors that could impact the effect of the intervention include the length of the follow‐up data collection period, the type of family violence complaint (e.g., intimate partner violence vs. elder abuse), and the sociodemographic characteristics of the victim and the offender (see generally Sherman, 2018). Ultimately, this review seeks not only to update the results of the prior review with additional research, but also to explore the mechanisms behind the observed effects in a way that provides utility for future policy creation.